Postpartum intrauterine contraceptive device: knowledge and factors affecting acceptance among postpartum women at tertiary care hospital in North-Western Rajasthan - K., Krishna; K., Swati; C., Shweta; N., Ankur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Intra-uterine contraceptive device (IUCD) insertion recommended within 10 min of placental delivery or within 48 hours of delivery is called postpartum IUCD according to WHO. Aim of the study was to evaluate the factors affecting knowledge and the likely acceptance of the postpartum intrauterine contraceptive device (PPIUCD). Methods: The present descriptive cross-sectional study was carried out in the Department of Obstetrics and Gynaecology at S. P. Medical College and associated group of hospitals, Bikaner, Rajasthan, India from May 2020 to July 2020. Total 500 post-partum women were studied with the help of predesigned and pretested questionnaire. Knowledge of the women was summarized as proportion. Chi-square test was used to compare proportions and univariate analysis for the factors affecting knowledge and likely adoption of PPIUCD. Results: The 210 (42%) women out of 500 women had knowledge regarding PPIUCD. Multiparity (p=0.003), education above secondary level OR=11.66 (95% CI=7.13-19.06), p=0.00, upper middle and middle socioeconomic status OR=6.77 (95% CI=4.44-10.16), p=0.00 and health worker counselling OR=13.61(95% CI=8.78-21.10), p=0.00 were significantly associated with knowledge. Multiparous women (p=0.004), women who had discussed PPIUCD with their husband (p<0.0001), women with family support for their decision (p<0.00001), women without religious beliefs (p<0.0001) were more significantly associated with adoption of PPIUCD. Conclusions: The level of knowledge of our study population regarding PPIUCD is 42%. Our study has reported education and regular health care worker counselling as most important modifiable predictors to improve the knowledge regarding PPIUCD.